UNTITLED - KING, ALEXANDER (Tufts Archival Research Center, 2007)
Letter from Alexander H. King to the Tobacco Institute confirming his acceptance of the position of consultant to the Tobacco Institute's Special Projects division. Discusses his salary and hourly wage as well as his responsibilities.